An Overview of Video Description: History, Benefits, and Guidelines. (March 2015) - Packer, Jaclyn; Vizenor, Katie; Miele, Joshua A.
This article provides an overview of the historical context in which video description services have evolved in the United States, a summary of research demonstrating benefits to people with vision loss, an overview of current video description guidelines, and information about current software programs that are available to produce video description.